Clinical utility of renal and urinary tract point-of-care ultrasound in the neonatal intensive care unit: insights from a case series - Gayatri Morajkar; Sujata Deshpande; Sachin Verma; Vivek Goyal; Jayanta Hazarika; Prasoon Bansal; Yogen Singh; Pradeep Suryawanshi (Frontiers in Pediatrics, 2026)
Background Clinical decision-making in acutely ill neonates often depends on the timely identification of the underlying pathology. Bedside point-of-care ultrasound (POCUS), performed by the treating clinician, allows immediate correlation of imaging findings with evolving clinical status. However, its role in evaluating renal and urinary tract abnormalities in neonates remains relatively underexplored and is not yet widely integrated into routine practice. Methods This multicenter case series included data from four tertiary neonatal intensive care units in India between January 2023 and March 2026. Neonates with acute clinical presentations in whom clinician-performed POCUS identified significant renal, adrenal, or urinary tract abnormalities were included. Ultrasound findings were interpreted alongside clinical and laboratory data and corroborated with formal imaging where required. Results Seven neonates with diverse clinical presentations were evaluated. POCUS identified a spectrum of infective, obstructive, hemorrhagic, and vascular pathologies involving the kidneys, bladder, and adrenal glands. Early detection with POCUS informed timely therapeutic decisions, including initiation of targeted antimicrobial or antifungal therapy, anticoagulation, relief of urinary obstruction, and appropriate conservative management. Serial examinations enabled ongoing assessment of disease evolution and response to treatment. Conclusion Clinician-performed renal and urinary tract POCUS provides actionable diagnostic information in acutely ill neonates and supports prompt, targeted management at the bedside. Its use may enhance clinical decision-making, particularly in time-sensitive situations where immediate access to comprehensive imaging is limited. These findings support incorporation of renal–urinary tract POCUS into structured neonatal POCUS training programs.